Satisfaction with the use of telehealth during COVID-19: An integrative review - Andrews, Elizabeth (Int J Nurs Stud Adv, 2020)
BACKGROUND: The novel coronavirus (COVID-19) pandemic has defined 2020 thus far. Businesses, social and religious gatherings, travel, and almost all forms of transportation shut down to halt the spread of COVID-19. People were ordered to quarantine in place, and the world appears to go into a standstill. In the midst of being quarantined people with acute and chronic conditions still require medical care and treatment. An alternative way for people to receive needed health care was necessary. Hence, we saw an unprecedented surge in telehealth. With this unprecedented surge in use of telehealth, there is matter of delivering quality care. OBJECTIVE: Guided by the Donabedian Model, the purpose of this integrative review was to examine current evidence on patient and healthcare provider's satisfaction with the use of telehealth during the COVID-19 pandemic. DESIGN: An integrative review of the literature DATA SOURCES: The literature review was conducted utilizing PubMED, CINAHL, Google Scholar and Cochrane Library databases. Inclusion criteria were studies published from January 2020 to July 11, 2020, published and translated in English language, and studies that evaluated patients and providers satisfaction with the use of telehealth or telemedicine during COVID-19. Eighteen articles were included in this review. REVIEW METHODS: An evaluation matrix was developed to collect data from the included articles. The articles were appraised using Fineout-Overholt & Gallagher-Ford Rapid Critical Appraisal Checklist for Descriptive Studies and Rapid Critical Appraisal of Evidence-Based Practice Implementation or Quality Improvement Projects (Melnyk & Fineout-Overholt, 2015). Authors independently appraised each article using the appropriate appraisal tools. RESULTS: Ten of the articles (53%) included were studies conducted in the United States. Sixteen out of 18 studies evaluated patient satisfaction and five studies examined healthcare providers’ satisfaction with the use of telehealth. The majority of telehealth services offered were by subspecialists. Overall, patients and healthcare providers have high level of satisfaction with the use of telehealth during COVID-19 pandemic. Many patients and healthcare providers reported willingness to continue using telehealth after the pandemic. CONCLUSION: This integrative review provided additional evidence on patient and healthcare provider's satisfaction with the use of telehealth. Findings in this review may not be surprising as individuals, healthcare providers, and health systems needed to adopt the use telehealth due to necessity. However, the results for telehealth are promising.